2018
DOI: 10.1002/mnfr.201801096
|View full text |Cite
|
Sign up to set email alerts
|

p107 Deficiency Increases Energy Expenditure by Inducing Brown‐Fat Thermogenesis and Browning of White Adipose Tissue

Abstract: Scope The tumor suppressor p107, a pocket protein member of the retinoblastoma susceptibility protein family, plays an important role in the cell cycle and cellular adipocyte differentiation. Nonetheless, the mechanism by which it influences whole body Energy homeostasis is unknown. Methods and Results The phenotype of p107 knockout (KO) mixed‐background C57BL6/129 mice phenotype is studied by focusing on the involvement of white and brown adipose tissue (WAT and BAT) in energy metabolism. It is shown that p10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Although many studies in mice revealed that browning of adipose tissue was associated with increased thermogenesis and energy expenditure leading to weight loss [37][38][39] , the browning effect of adipose tissue associated with increased energy expenditure and weight loss in humans is still under debate. After mild cold exposure, human subjects with high brown adipose tissue mass increased daily energy expenditure by 14.7% while subjects with low brown adipose tissue mass slightly increased their energy expenditure by 0.4% 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies in mice revealed that browning of adipose tissue was associated with increased thermogenesis and energy expenditure leading to weight loss [37][38][39] , the browning effect of adipose tissue associated with increased energy expenditure and weight loss in humans is still under debate. After mild cold exposure, human subjects with high brown adipose tissue mass increased daily energy expenditure by 14.7% while subjects with low brown adipose tissue mass slightly increased their energy expenditure by 0.4% 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Several TFs and activating cofactors are shown to have negative effects on beige/brown fat formation and function including Hes1 [ 122 ], Irx3 [ 123 ], Irx5 [ 123 ], Rip140 [ 124 , 125 , 126 ], Tle3 [ 127 ], Zfp423 [ 128 , 129 ], Hoxc8 [ 130 ], Hoxc10 [ 131 ], Twist1 [ 132 ], Foxa3 [ 133 , 134 ], Foxo1 [ 135 , 136 ], Foxp1 [ 137 ], Rb [ 138 ], Src2 (Tif2), Smad3 [ 139 ], Usf1 [ 140 ], Mrtfa [ 141 ], Lxr [ 142 ], and P107 [ 143 , 144 , 145 ]. Transcriptional repressors such as Ctbp1 and Ctbp2 [ 90 , 146 ] suppress the WAT gene expression and promote the browning of WAT.…”
Section: Molecular Circuits Regulating Brown and Beige Adipose Tissue Development And Functionmentioning
confidence: 99%
“…Several TFs and activating cofactors are shown to have negative effects on beige/brown fat formation and function including Hes1 [122], Irx3 [123], Irx5 [123], Rip140 [124][125][126], Tle3 [127], Zfp423 [128,129], Hoxc8 [130], Hoxc10 [131], Twist1 [132], Foxa3 [133,134], Foxo1 [135,136], Foxp1 [137], Rb [138], Src2 (Tif2), Smad3 [139], Usf1 [140], Mrtfa [141], Lxr [142], and P107 [143][144][145]. Transcriptional repressors such as Ctbp1 and Ctbp2 [90,146] suppress the WAT gene expression and promote the browning of WAT.…”
Section: Transcriptional Regulation Of Brown and Beige Adipocytesmentioning
confidence: 99%